Including health impacts in environmental impact assessments for three Australian coal-mining projects: a documentary analysis. (5th May 2019) - Riley, Emily; Sainsbury, Peter; McManus, Phil; Colagiuri, Ruth; Viliani, Francesca; Dawson, Angus; Duncan, Elizabeth; Stone, Yolande; Pham, Tracy; Harris, Patrick
Abstract: Notwithstanding the historical benefits of coal in aiding human and economic development, the negative health and environmental impacts of coal extraction and processing are of increasing concern. Environmental impact assessments (EIAs) are a regulated policy mechanism that can be used to predict and consider the health impacts of mining projects to determine if consent is given. The ways in which health is considered within EIA is unclear. This research investigated 'How and to what extent are health, well-being and equity issues considered in Environmental Impact Assessments (EIAs) of major coal mining projects in New South Wales, Australia'. To this end we developed and applied a comprehensive coding framework designed to interrogate the publicly available environmental impact statements (EISs) of three mines in New South Wales (NSW), Australia, for their inclusion of health, well-being and equity issues. Analysis of the three EISs demonstrates that: the possible impacts of each mine on health and well-being were narrowly and inadequately considered; when health and well-being were considered there was a failure to assess the possible impacts specific to the particular mine and the communities potentially affected; the cumulative impacts on human health of multiple mines in the same geographical area were almost completely ignored; the discussions of intragenerational and intergenerational equity did not demonstrate a sound understanding of equity and, it is essential that governments' requirements for the EIA include detailed analysis of the health, well-being, equity and cumulative impacts specific to the proposed mine and relevant communities.